Model characteristics and senior students training structure in military-sports round - Dykyi, Oleh (Journal of Education, Health and Sport, 2017)
Model characteristics and senior students training structure in military-sports round are being considered in this article. It is settled that the average index in pulling up on the bar is 17.07 times, in overcoming the obstacle bar is 2 minutes 09 seconds, in running 100 meters is 13.01 seconds, in running 3000 meters is 11 minutes 31 seconds, in swimming is 41.01 seconds, in throwing grenades is 40.89 meters and in shooting is 49.27 points. The average sum of points is 3536.03. Stage-by-stage successive training method is used for training in military-sports round. General physical training with the accent on speed and endurance development had been organized for the first 4 weeks. Physical exercises for improvement in throwing the grenade, swimming, running 3000 meters and pulling up on the bar dominated during the second stage of the training (6 weeks). Overcoming the obstacle bar and shooting were added to those physical activities at the third stage.